Indigenous performance and modernity : investigating the vitality of play and work songs of the Dagaaba community in North Western Ghana as verbal art performance - Ismaila, Margaret (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.